1983
DOI: 10.1007/bf02469514
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactive carcinoembryonic antigen in gastric juice in patients with gastric cancer

Abstract: To clarify the significance of immunoreactive carcinoembryonic antigen in gastric juice (gastric CEA) from gastric cancer patients, we studied the gastric CEA in comparison with cancer progress, histologic types of tumors, staining for CEA and extent of intestinal metaplasia. The gastric CEA levels from patients with other gastric diseases, i.e., gastric ulcer, duodenal ulcer and chronic gastritis were also investigated. The mean gastric CEA level from gastric cancer patients was significantly higher than from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
2

Year Published

1988
1988
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
2
5
2
Order By: Relevance
“…CEA is also well known as a tumour marker in gastric cancer. It has been reported that serum levels and tissue expression of this protein correlate with evidence of tumour progression, such as lymph node metastasis, in keeping with our results (Kojima et al, 1984;Nakane et al, 1994;Kim et al, 2000). Nonspecific crossreacting antigen is a member of the CEA family …”
Section: Discussionsupporting
confidence: 92%
“…CEA is also well known as a tumour marker in gastric cancer. It has been reported that serum levels and tissue expression of this protein correlate with evidence of tumour progression, such as lymph node metastasis, in keeping with our results (Kojima et al, 1984;Nakane et al, 1994;Kim et al, 2000). Nonspecific crossreacting antigen is a member of the CEA family …”
Section: Discussionsupporting
confidence: 92%
“…In this study, 231 out of 325 patients (71.1%) were positive for CEA. This figure is similar to that obtained by Kojima et al [30], however it is much greater than the values of Santeusanio et al [31], Tanioku [32], and Goldemberg et al [33]. The disparity between these investigations can be explained by the heterogeneity of CEA itself and by the different CEA sites recognized by antisera employed [35].…”
Section: Discussionsupporting
confidence: 86%
“…Measuring the serum CEA level is a common procedure [30][31][32], but this parameter is not strongly correlated with tumor progression, because CEA is inactivated in the liver and the serum level is usually normal in gastric carcinoma patients unless they have liver or lymph node metastases [33]. Therefore, measuring CEA at the cellular level is required to better assess the malignant potential of a cancer.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Kodera et al (7) reported that preoperative serum CEA was not an independent prognostic factor. Concerning the expression of CEA in cancer tissues, Kojima et al (16) reported in a study on 162 cases that a higher 5-year survival rate was shown in the group of patients with tumor stained as negative or weakly positive than in the group stained as strong positive, nevertheless, contradictory results have been also reported (17). In the current study, the expression of CEA in tissues was not associated with the recurrence rate as well as 5-year survival rate.…”
Section: Discussioncontrasting
confidence: 49%
“…Immunohistochemical staining method could be applied to formalin fixed tissues prepared for hematoxylin-eosin staining, its result could be obtained rapidly because the staining procedure is relatively simple, and the burden of the exposure to radiation is absent, and thus it has been used widely (16,17).…”
Section: Introductionmentioning
confidence: 99%